2021
DOI: 10.5614/j.eng.technol.sci.2021.53.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Yield of Powder and Bioactive Materials during Extraction and Spray Drying of Dragon Fruit Skin Extracts

Abstract: One potential utilization of dragon fruit skin is to produce bioactive materials as natural antioxidants and colorants for the food industry by extraction and spray drying. This study investigated the quality (total phenolic compounds/TPC, betacyanin and betaxanthin contents, and antioxidant activity) of the extracts and spray-dried products, and the quantity (powder yield) obtained by the use of different types and amounts of spray drying agents. Two drying agents were introduced during spray drying, i.e. mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These results agree with the findings of Adetoro et al [ 10 ], who reported the highest yield of freeze-dried pomegranate juice powder from MT. The lower yield from WS-encapsulated powder could be due to the crystals formed by the waxy starch-based powder [ 20 ] The PFPP production yield in the present study (13.02–15.40%) was lower when compared to the yield of eggplant peel extract powder (39.58 to 66.47%) and dragon fruit peel extract powder (72.70%) developed using MT, and these dissimilarities could be ascribed to the variation in the encapsulation techniques, and the concentration of the carriers [ 12 , 21 ].…”
Section: Resultsmentioning
confidence: 94%
“…These results agree with the findings of Adetoro et al [ 10 ], who reported the highest yield of freeze-dried pomegranate juice powder from MT. The lower yield from WS-encapsulated powder could be due to the crystals formed by the waxy starch-based powder [ 20 ] The PFPP production yield in the present study (13.02–15.40%) was lower when compared to the yield of eggplant peel extract powder (39.58 to 66.47%) and dragon fruit peel extract powder (72.70%) developed using MT, and these dissimilarities could be ascribed to the variation in the encapsulation techniques, and the concentration of the carriers [ 12 , 21 ].…”
Section: Resultsmentioning
confidence: 94%